Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae) - Azevedo, Renato A.; Sobral, Rafael; Dambros, Cristian S.; Morais, José W. De (Zootaxa, 2017)
The neotropical termite genus Neocapritermes Holmgren (1912) was revised by Krishna & Araujo (1968), who recognized 14 valid species. Two additional species were described by Constantino (1991), and another one by Bandeira & Cancello (1992). However, the imago of most species of Neocapritermes remain unknown. In this paper we describe for the first time the imago of Neocapritermes utiariti based on specimens from the State of Rondônia, Brazil. The examined material will be deposited in the Invertebrate Collection of the Instituto Nacional de Pesquisas da Amazônia, in Manaus, Amazonas, Brazil (INPA). Comparisons with other imagoes of Neocapritermes were made based on descriptions and figures from Krishna & Araújo (1968). The measurements were taken with an ocular micrometer following Roonwal’s (1970) system of morphometric characters.